HARNESSING ARTIFICIAL INTELLIGENCE FOR GOVERNANCE EFFICIENCY IN FCT, ABUJA - Adedeji Daniel Gbadebo (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The study investigates the use of artificial intelligence (AI) to improve government efficiency in the Federal Capital Territory (FCT), Abuja. The study, based on Socio-Technical Systems (STS) Theory, investigates the interaction between technical breakthroughs and social systems in governance. The study used a survey method where a structured questionnaire was given to 385 respondents by stratified random sampling, with data analyzed using the chi-square statistical method. The findings show that AI greatly enhances decision-making and service delivery, with 71% of participants believing in its revolutionary potential. Inadequate infrastructure and a lack of technical skills are among the key concerns cited. The study emphasizes the necessity for strong digital frameworks, capacity building, and ethical concerns in AI integration. Infrastructure improvements, focused AI training for public authorities, and small-scale pilot projects in healthcare, transportation, and urban management are among the recommendations made to foster citizen trust and inclusion. The findings provide policymakers with concrete insights into using AI as a catalyst for successful governance in Abuja, promoting transparency, responsiveness, and economic growth.